What we did in bed : a horizontal history - Fagan, Brian M.; Durrani, Nadia (Yale University Press, 2019)
Pulling back the covers on the fascinating, yet often forgotten, history of the bed. Louis XIV ruled France from his bedchamber. Winston Churchill governed Britain from his during World War II. Travelers routinely used to bed down with complete strangers, and whole families shared beds in many preindustrial households. Beds were expensive items-and often for show. Tutankhamun was buried on a golden bed, wealthy Greeks were sent to the afterlife on dining beds, and deceased middle-class Victorians were propped up on a bed in the parlor. In this sweeping social history that covers the past seventy thousand years, Brian Fagan and Nadia Durrani look at the endlessly varied role of the bed through time. This was a place for sex, death, childbirth, storytelling, and sociability as well as sleeping. But who did what with whom, why, and how could vary incredibly depending on the time and place. It is only in the modern era that the bed has transformed into a private, hidden zone, and its rich social history has largely been forgotten.